A Comment on Pluripotent Stem Cells in Next-Generation Biomedical Theranostics - Rossbach, M. (Current Molecular Medicine, 2013)
New developments in DNA sequencing platforms and the advancements in GWAS studies (genome-wide association studies) are changing the understanding of human pathologies. Such developments will ultimately result in a deeper understanding of how genomic variations contribute to diseases. Induced pluripotent stem cells (iPSCs) are currently entering clinical research phases, allowing the investigation of disease pathways and the identification of new targets and potentially druggable biomarkers. IPSCs can serve as a model for studying human diseases as they retain all the genetic information from a patient; iPSC-derived cells can be used as a tool for drug screening or discovery. In combination with next generation sequencing (NGS)-based and GWAS technologies, iPSCs have the potential to become a novel platform technology to predict adverse drug and off-target effects, and using such cell models to predict toxicity. In view of the arising concepts of regenerative theranostics, iPSCs and NGS technologies provide a powerful means to analyze the complexity of diseases on the molecular level and to better understand the processes that lead to pathobiology. To promote the widespread use of iPSC-based approaches in drug development it has to be shown that the cells can be reliably produced in the quantity, consistency and purity needed to meet pharmaceutical standards. Integrative genomics and genetic approaches have shown to be a useful tool in elucidating the complexity found in gene regulatory pathways. In this review, the application of pluripotent stem cells for the generation of next-generation theranostics and newer perspectives on iPSCs in modeling clinical diseases, are discussed.
Keywords: personalized medicine